2001
DOI: 10.1007/s11882-001-0035-1
|View full text |Cite
|
Sign up to set email alerts
|

Cockroach allergens: Environmental distribution and relationship to disease

Abstract: Cockroach allergy has been recognized as an important cause of asthma. Exposure to high levels of cockroach allergens in the home is a major risk factor for symptoms in sensitized individuals. Previously identified allergens from Blatella germanica and Periplaneta americana include Bla g 2 (inactive aspartic proteinase), Bla g 4 (calycin), Bla g 5 (glutathione-S-transferase), Bla g 6 (troponin), the Group 1 cross-reactive allergens Bla g 1 and Per a 1, Per a 3 (arylphorin), and Per a 7 (tropomyosin). The prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 43 publications
1
17
0
3
Order By: Relevance
“…A presença de reatividade cruzada entre esses alérgenos é a justificativa mais plausível. Eles apresentam em comum a tropomiosina, proteína contrátil presente tanto nos ácaros quanto na barata e nos pescados (camarão) 25 . Outra concomitância de positividade foi a do leite de vaca e do epitélio de vaca.…”
Section: Controles Alérgicosunclassified
“…A presença de reatividade cruzada entre esses alérgenos é a justificativa mais plausível. Eles apresentam em comum a tropomiosina, proteína contrátil presente tanto nos ácaros quanto na barata e nos pescados (camarão) 25 . Outra concomitância de positividade foi a do leite de vaca e do epitélio de vaca.…”
Section: Controles Alérgicosunclassified
“…The allergenic structures of the diVerent cockroach species are well known (Arruda et al 2001). Some cockroach allergens show a high homology to allergens of other species (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that 55% of children and young adults with allergic respiratory symptoms had a positive skin test reaction to cockroach allergens in Brazil [126]. Children with asthma who were sensitized and exposed to high levels of cockroach allergens had increased asthma morbidity [127].…”
Section: Cockroach Allergens and Asthmamentioning
confidence: 99%